Analisis Kandungan Serat pada Snack Bar Substitusi Tepung Bekatul dan Tepung Mocaf Bagi Penderita Obesitas - Sholikhatul Uma; Dian Ayu Ainun Nafies (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Background: Obesity is a condition where there is excessive accumulation of fat in the body that occurs when the amount of energy consumed is too large compared to the amount of energy expended, causing body weight far above normal and can be harmful to health. To provide additional fiber to adolescents, it is expected that the manufacture of a rice bran flour and mocaf flour substitution snack bar can be used as an alternative high-fiber snack for adolescents. Purpose: The purpose of this study was to determine the effect of rice bran flour and mocaf flour substitution on the fiber content of snack bars. Method: This type of research uses True Experimental with a Completely Randomized Design (CRD) with 4 treatment levels and 6 replications. The treatment carried out was by comparing the proportion of wheat flour: rice bran flour: mocaf flour in each P0 (100:0:0), P1 (0:20:80), P2 (0:50:50), P3 (0:80:20). Results: The results of the study showed that there was an effect of increasing fiber levels in snack bars, the more bran flour was added, the more fiber levels increased, with the highest fiber levels in treatment P3, which was 11.88 gr. Conclusion: There was a tendency for the addition of bran flour, the more bran flour was added, the more fiber levels in snack bars increased.